PENGEMBANGAN BAHAN AJAR BERBENTUK BUKU CERITA BERGAMBAR BERBASIS SAINTIFIK PADA MATA PELAJARAN FISIKA KELAS XI IPA SMA NEGERI MEGANG SAKTI - Umi Solehah; Ahmad Amin; Endang Lovisia (LP4MK STKIP PGRI Lubuklinggau, 2023)
This study aims to develop teaching materials in the form of scientific-based picture story books in physics subjects before being used. This research uses development research based on the 4D model (Define, Design, Develop, and Disseminate). At the development stage (Develop). The validation assessment was carried out by media experts, material experts and language experts. The validation results of media experts scored 40 in the very good category, material experts scored 50 and linguists scored 27. So it can be concluded that the development of teaching materials in the form of picture story books based on scientific physics for class XI IPA students at SMA Negeri Megang Sakti is very good from aspects of media, material and discussion reach valid criteria.